Szegö polynomials: quadrature rules on the unit circle and on [-1, 1] - Bressan, R. [UNESP]; Menegasso, S. F. [UNESP]; Sri Ranga, A. [UNESP] (Rocky Mt Math Consortium, 2003)
We consider some of the relations that exist between real Szegö polynomials and certain para-orthogonal polynomials defined on the unit circle, which are again related to certain orthogonal polynomials on [-1, 1] through the transformation x = (z1/2+z1/2)/2. Using these relations we study the interpolatory quadrature rule based on the zeros of polynomials which are linear combinations of the orthogonal polynomials on [-1, 1]. In the case of any symmetric quadrature rule on [-1, 1], its associated quadrature rule on the unit circle is also given.